Environmental Health Risk Analysis of Exposure To Cadmium in Local Water Company Tirta Anoa Water Communities in The Mandonga District Area, Kendari City - Juliyanti, Juliyanti; Azizi Jayadipraja, Erwin; Adi Surya, Ridwan (Magister Kesehatan Universitas Mandala Waluya, 2024)
Introduction: Local Water Company in Kendari city has 4 sources, namely the Konaweha (Pohara) river, Wanggu river, Anggoeya river, Matabondu spring. The Konaweha River is one of the rivers that has a high potential for being polluted by nickel mining activities. Based on the results of research conducted by (Hasani, 2017), the Konaweha river is in the lightly polluted category. The presence of heavy metals in the environment causes accumulation in aquatic biota. Method: This research uses quantitative research in the form of a descriptive survey with a cross sectional research design. Analytically, data from variable measurements is analyzed using the Environmental Health Risk Analysis formula to determine health risks due to exposure to lead in community drinking water and risk management from cadmium pollution to public health. Result: Description of cadmium concentration in Local Water Company Tirta Anoa water, Mandonga subdistrict, Kendari city after sampling and laboratory testing at 3 points, namely the first point in Mandonga sub-district with a cadmium concentration of 0.002 mg/L, the second point in Korumba sub-district with a cadmium concentration of 0.001 mg/L , and at the third point in Anggilowu sub-district with a cadmium concentration of 0.002 mg/L. Conclusion: The conclusion in this journal The respondent's risk level based on the RQ calculation value is still < 1, which means that people who receive water from Local Water Company Tirta Anoa, Kendari City in the Mandonga sub-district area have no risk of health problems now and in the next 30 years.